The learner-centered classroom and school : strategies for increasing student motivation and achievement - McCombs, Barbara L. 4 0 16; 1941- Whisler, Jo Sue; 5 (San Francisco : Jossey-Bass, 1997)
Describes the learner-centered model for creating schools and classrooms that foster student motivation, learning, and achievement; addressing specific features and characteristics of the system, and discussing what it takes to move toward a learner-centered design.
Includes bibliographical references and index.
Adult.
Keywords: 2 -- 0; 6; Administration. -- Educational innovations;Learning, Psychology of.;Classroom environment;Motivation in education;Academic achievement;Educational change.;Academic achievement.;Psychology of learning.;Schools -- United States.;United States.;United States.;United States; 20; 2